Inflammation-associated drug resistance and tumor growth in TNBC - Hassan, Arij Fouzat; Kheraldine, Hadeel; Abujamous, Lama; Al-Thawadi, Hamda; Elhissi, Abdelbary (Frontiers in Immunology, 2025)
Triple-negative breast cancer (TNBC) is an aggressive and clinically challenging subtype of breast cancer characterized by the absence of hormone receptors and HER2 amplification. This molecular profile limits the effectiveness of targeted therapies, leaving chemotherapy as the mainstay of treatment a strategy often met with limited success due to rapid disease progression and high recurrence rates. Increasing evidence underscores the pivotal role of the tumor microenvironment (TME) in driving TNBC pathogenesis, particularly through chronic inflammation and cytokine dysregulation. Inflammatory cytokines such as TNF-α, TGF-β, IL-6, and IL-10 orchestrate a complex network of cellular interactions that remodel the TME into an immunosuppressive niche. This inflammatory landscape not only promotes tumor cell proliferation and metastasis but also compromises antitumor immune responses and contributes to therapeutic resistance. Recent preclinical and clinical studies have explored the therapeutic potential of targeting cytokine signaling to disrupt this inflammatory axis and overcome resistance. In this review, we critically examine the multifaceted interplay between cytokines, inflammation, and the TME in TNBC, with a focus on mechanisms of resistance. We further evaluate current and emerging therapeutic approaches targeting the inflammatory axis, highlighting both the promise and the complexities of this evolving landscape.